EVALUASI VALIDITAS KIT RAPID DIAGNOSTIC TEST ANTIGEN (RDT-Ag) SARS-CoV-2 - Rizana Fajrunni'mah (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2022)
The COVID-19 pandemic is still ongoing around the world. The rapid and easy development and validation of diagnostic methods is a top priority in response to the handling of the COVID-19 pandemic. The study aimed to evaluate the performance of the SARS-CoV-2 Antigen Rapid Diagnostic Test (RDT-Ag). The RDT-Ag kits evaluated in the study were RDT-Ag VD, RDT-Ag GB kits, and RDT-Ag TS kits that included sensitivity and specificity values. rRT-PCR and RDT-Ag tests use 90 samples of the same nasopharyngeal or oropharyngeal swab. The samples included 30 positive samples (Ct ≤ 25), 30 positive samples (Ct 25), and 30 negative samples. Then, the results of rRT-PCR are used as a standard reference for RDT-Ag evaluation. RDT-Ag VD kit obtained 80% sensitivity in the positive sample group with a Ct value of ≤25, and 10% in the positive sample group with a Ct value of 25 with 93.3% specificity. The RDT-Ag GB kit obtained 70% sensitivity in the positive sample group with a Ct value of ≤ 25, and 10% in the positive sample group with a Ct value of 25 with 100% specificity. The RDT-Ag TS kit obtained 93.3% sensitivity in the positive sample group with a Ct value of ≤25, and 20% in the positive sample group with a Ct value of 25 with 100% specificity. The sensitivity of RDT-Ag compared to the rRT-PCR results increased in the sample with a Ct value of ≤25 ( 70%) and its sensitivity decreased dramatically in the sample with a Ct value of 25 ( 20%).